Game development with blender - Felinto, Dalai; Pan, Mike. (Boston : Cengage Learning PTR, 2014)
A guide to the Blender game engine, spanning topics ranging from logic brick and physics to graphics, animation, scripting, and more.
Game blender in a nutshell -- First game -- Logic bricks -- Animation -- Graphics -- Physics -- Workflow and optimization -- Publishing and beyond -- Case studies.
Includes index.
Adult.
Adult
Keywords: Blender (Computer file); Blender (Computer file); Computer animation -- Computer programs; Computer animation -- Computer software; Computer graphics -- Computer programs; Computer graphics -- Computer software; Three-dimensional display systems; Three-dimensional display systems; Video games -- Design; Video games -- Design